2020
DOI: 10.1590/0004-282x20200070
|View full text |Cite
|
Sign up to set email alerts
|

Primary headache subtypes and thyroid dysfunction: Is there any association?

Abstract: Background: Primary headaches, and particularly migraine and tension-type headache (TTH) as well as hypothyroidism are common medical conditions. To date, numerous studies have suggested a possible bidirectional relationship between migraine and hypothyroidism, although certain studies had contradictory results. Objective: To investigate whether there is any association between primary headache subtypes and thyroid disorders. Methods: A retrospective study of consecutive patients aged ≥18 years referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…There is uncertainty on association of thyroid disorders and headaches with some studies reporting no association and other studies reporting a higher prevalence of primary headache disorders such as migraine in patients with thyroid dysfunction; primarily hypothyroidism (29)(30)(31)(32).…”
Section: Thyroid Disordersmentioning
confidence: 99%
“…There is uncertainty on association of thyroid disorders and headaches with some studies reporting no association and other studies reporting a higher prevalence of primary headache disorders such as migraine in patients with thyroid dysfunction; primarily hypothyroidism (29)(30)(31)(32).…”
Section: Thyroid Disordersmentioning
confidence: 99%
“…Observational epidemiological studies indicate an increased cooccurrence of migraine and thyroid dysfunction [19][20][21][22][23][24][25][26][27][28][29][30]. For example, some recent studies have reported an increased chance of hypothyroidism onset in cases with migraine/headache disorders [19][20][21][22][23].…”
Section: Epidemiolog Ic Al S Tudie Smentioning
confidence: 99%
“…The strengths of the reviewed studies include the following: (i) the majority of the migraine studies utilized standardized diagnostic criteria using the International Classification of Headache Disorders (ICHD) [19,21,22,24,25,[27][28][29] and two studies recruited patients from headache centres [19,29], whilst the diagnoses of thyroid function and dysfunction were based on laboratory measurements [25][26][27][28][29] and a few studies recruited patients from endocrine centres [25][26][27]; (ii) large population-based studies allowed for generalization of headache prevalence in the population [20,23,28]; and (iii) Seidkhani-Nahal et al, using the Bradford Hill criteria [31] to determine causality, reported a strong association between migraine and thyroid dysfunction [30]. Limitations potentially leading to false positive and negative results include (i) the use of heterogeneous migraine diagnoses across studies, such as migraine diagnosis based on questionnaires [20], patient self-report, general physician's diagnosis and use of headache-specific medications [23], and not stating the method of migraine diagnosis [26]; (ii) thyroid diagnosis on the basis of patient self-report [19,20,24], although Le et al noted that self-reported thyroid disorders were probably correct [20]; and (iii) diagnosis of hypothyroidism (measuring the levels of T3, T4 and TSH) in Martin et al varied during the study period [23].…”
Section: Epidemiolog Ic Al S Tudie Smentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prevalence of HT in the general population is high and still growing, there is a lack of data regarding migraine and HT connection. Hence, we found only one work that examined the presence of different types of headaches in HT patients and one regarding the prevalence of HT in migraine patients ( 14 , 15 ). Because of this, and based on our clinical observations, we aimed to retrospectively analyze the prevalence of Hashimoto’s thyroiditis among migraine sufferers visiting our specialized headache clinic considering the clinical characteristics of patients with this disease, including migraine severity.…”
Section: Introductionmentioning
confidence: 99%